Building Prestige Values for Eatsambel Products through Instagram Advertising: A Critical Discourse Analysis - Nadia, Intan; Basri, Irfani (Journal of Languages and Language Teaching, 2025)
This study aims to analyze how prestige value is built through Eatsambel product advertisements on Instagram, focusing on thematic, schematic, and semantic aspects. A qualitative approach is used, where Teun A. van Dijk's critical discourse analysis is applied to explore the key elements used in the advertisement. The data was taken from Eatsambel's Instagram posts in the period from November 2023 to January 2024, covering various advertising campaigns. The results show that themes such as quality of ingredients, authenticity of the manufacturing process, and rich culinary culture are used to build a prestigious image. Elegant visual schemes and narratives relevant to everyday life were also found to be strategies to reinforce the image of exclusivity. Semantic aspects, such as word choice that emphasizes the superiority of taste, also play a role in shaping the perception of the product's prestige in the eyes of the audience. The combination of these elements creates a comprehensive marketing approach, where prestige value is not only built through exclusivity, but also through proximity to the audience. The findings have important implications for marketing strategies in the culinary industry, demonstrating that the integration between digital elements and prestige imagery can increase product appeal and strengthen emotional connections with consumers. The research encourages the development of dynamic and relevant advertising narratives, combining traditional and innovative elements to reach a wider market segment.